Relationships Between Age, Frailty, Length of Care Home Residence and Biomarkers of Immunity and Inflammation in Older Care Home Residents in the United Kingdom - Castro-Herrera, Vivian M.; Lown, Mark; Fisk, Helena L.; Owen-Jones, Eleri; Lau, Mandy; Lowe, Rachel; Hood, Kerenza; Gillespie, David; Hobbs, F. D. Richard; Little, Paul; Butler, Christopher C.; Miles, Elizabeth A.; et al. (Frontiers in Aging, 2021)
Ageing entails changes to the immune system, collectively termed immunosenescence and inflammageing. The relationships among age, frailty and immune parameters in older people resident in care homes deserves better exploration. We assessed immune and inflammatory parameters in UK care home residents aged over 65 yr and how they relate to age, frailty index and length of care home residence. Linear regression was used to identify the independent contribution of age, frailty and length of care home residence to the various immune parameters as dependent variables. Participants had a mean age (+ SD) of 85.3 ± 7.5 yr, had been residing in the care home for a mean (+ SD) of 1.9 ± 2.2 yr at the time of study commencement, 33.2% were severely frail. Length of care home residence and frailty index were correlated, age and frailty index, and age and length of care home residence were not significantly correlated. All components of the full blood count, apart from total lymphocytes, were within the reference range; 31% of participants had blood lymphocyte numbers below the lower value of the reference range. Among the components of the full blood count, platelet numbers were positively associated with frailty index. Amongst plasma inflammatory markers, C-reactive protein (CRP), interleukin-1 receptor antagonist (IL-1ra), soluble E-selectin and interferon gamma-induced protein 10 (IP-10) were positively associated with frailty. Plasma soluble vascular cell adhesion molecule 1 (sVCAM-1), IP-10 and tumor necrosis factor receptor II (TNFRII) were positively associated with age. Plasma monocyte chemoattractant protein 1 was positively associated with length of care home residence. Frailty was an independent predictor of platelet numbers, plasma CRP, IL-1ra, IP-10 and sE-selectin. Age was an independent predictor of activated monocytes and plasma IP-10, TNFRII and sVCAM-1. Length of care home residence was an independent predictor of plasma MCP-1. This study concludes that there are independent links between increased frailty and inflammation and between increased age and inflammation amongst older people resident in care homes in the UK. Since inflammation is known to contribute to morbidity and mortality in older people, causes and consequences of inflammation in this population should be further explored.